Chiral coordination polymers based on d10 metals and 2-aminonicotinate with blue fluorescent/green phosphorescent anisotropic emissions. Issue 26 (19th June 2018) - Pajuelo-Corral, Oier; Rodríguez-Diéguez, Antonio; García, Jose A.; San Sebastián, Eider; Seco, Jose M.; Cepeda, Javier
Abstract : Two isostructural and chiral 2D-layered coordination polymers present bright blue steady-state fluorescence that turns into pale green long-lasting phosphorescence. Abstract : Herein, we report the detailed structural characterization and photoluminescence (PL) properties of two new isostructural coordination polymers (CPs) based on 2-aminonicotinate (2ani) ligand and zinc(ii ) or cadmium(ii ) metal ions, namely, [M(μ-2ani)2 ] n [M II = Zn(1 ) and Cd(2 )]. These compounds are characterized as chiral 2D-layered structures, resulting from the bridging of the 2ani ligands in the MN2 O4 coordination shell. Also, strong supramolecular interactions are found to sustain the overall crystal structure, which endows these materials with high stability. The single crystals of1 exhibit waveguiding behaviour along some preferred orientations. The examination of the polycrystalline samples of both compounds under UV light also shows that the samples exhibit remarkably strong PL emissions, which consist of blue fluorescence and green phosphorescence involving long-lasting phosphorescence (LLP) at low temperature. Fitting of the decay curves confirms the occurrence of short (in the order of nanoseconds) and very large lifetimes ( τ ≈ 320 and 560 ms for1 and2, respectively) of the wavelengths responsible for their blue and green emissions, respectively, which have been studied using DFT calculations.